Evaluasi Tata Kelola Teknologi Informasi di Perpustakaan Perguruan Tinggi dengan COBIT 5 - Mambang; Finki Dona Marleny; Wulandari Febriani; Theresia Kurniati Seran; Nalo Valentino (Jurnal Informasi dan Teknologi, 2022)
The COBIT 5 framework can be implemented in all organizations or enterprises. This study analyzes and finds the maturity level of IT governance in the XYZ Library. Libraries have a role in encouraging the efficiency and effectiveness of the learning process. The IT governance element in COBIT 5 aims to get results from evaluating stakeholders' needs, conditions and choices. Survey and in-person interviews are methods of obtaining data and information from the IT governance process at the XYZ Library. The COBIT 5 domains used are evaluated, direct, and monitored (EDM) and align, plan and organize (APO) domains. The results of the evaluation that have been carried out show the findings of gaps in the process domain EDM01 with a value of 2.34 and EDM04 with a gap of 2.25. While in the process domain, APO01 with a gap of 2.13, and APO07 with a gap of 2.34. With the average value of the entire gap at the level of 2.26, the findings of the XYZ Library with the process domains EDM01, EDM04, APO01, and APO07 show that the process is managed and the results are determined, controlled, and maintained (Managed). For further research, we can add more process domains both in the Governance and Management areas so that the audit process with the COBIT 5 framework can be carried out comprehensively.